2013
DOI: 10.1007/s11064-013-1145-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations on Na+,K+-ATPase and Acetylcholinesterase Activities Induced by Amyloid-β Peptide in Rat Brain and GM1 Ganglioside Neuroprotective Action

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder whose pathogenesis involves production and aggregation of amyloid-β peptide (Aβ). Aβ-induced toxicity is believed to involve alterations on as Na(+),K(+)-ATPase and acetylcholinesterase (AChE) activities, prior to neuronal death. Drugs able to prevent or to reverse these biochemical changes promote neuroprotection. GM1 is a ganglioside proposed to have neuroprotective roles in AD models, through mechanisms not yet fully understood. Therefore, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…This result was not expected, as many works have already shown that Aβ-treated animals normally present increases in AChE activity. However, in those works, the doses used were at least 32 times higher (0.159 nmol/μL to 2,0 nmol/ μL) than the dose used in the present work (0.005 nmol/μL) and the researchers made a single injection (or three single injections) of the Aβ (1–40 or 1–42), and not a chronic infusion [47,48,49,50,51]. In previous works, our research team observed neuron degeneration in the cortex and hippocampus and loss of memory in animals infused with 0.005 nmol/μL [18,19,29,52].…”
Section: Resultsmentioning
confidence: 81%
“…This result was not expected, as many works have already shown that Aβ-treated animals normally present increases in AChE activity. However, in those works, the doses used were at least 32 times higher (0.159 nmol/μL to 2,0 nmol/ μL) than the dose used in the present work (0.005 nmol/μL) and the researchers made a single injection (or three single injections) of the Aβ (1–40 or 1–42), and not a chronic infusion [47,48,49,50,51]. In previous works, our research team observed neuron degeneration in the cortex and hippocampus and loss of memory in animals infused with 0.005 nmol/μL [18,19,29,52].…”
Section: Resultsmentioning
confidence: 81%
“…However, it is not clear whether the atypical histochemical behavior of AChE observed in AD is due to alterations in kinetic properties of these enzymes (Ciro et al, 2012), or due to interactions with other molecules within these lesions (Darvesh et al, 2010). In the context of the presence of AChE within plaques and NFT, it is important to note that both AD effectors, Aβ and abnormally hyperphosphorylated tau, can influence AChE levels in vitro (Sberna et al, 1997;Sáez-Valero et al, 2003;Hu et al, 2003;Melo et al, 2003) and in rodent models (Sberna et al, 1998;Sáez-Valero et al, 2002;Silveyra et al, 2012b;Kreutz et al, 2013). We have also demonstrated that Aβ alters AChE glycosylation in vivo (Sberna et al, 1998;Fodero et al, 2002), and this change is similar to the change in the glycosylation pattern of AChE in AD brain 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, phosphorylation at Ser8 may change the interaction of Aβ with other proteins, such as Na + ,K + -ATPase. Previously, it was shown that Na + ,K + -ATPase activity was inhibited in post-mortem tissues of AD patients and in amyloid-containing hippocampi of transgenic mice (but not in the amyloid-free cerebellum) (Dickey et al, 2005; Kreutz et al, 2013; Zhang et al, 2013). The latest studies demonstrated that Aβ 42 in form of monomers or oligomers directly binds to Na + ,K + -ATPase, which results in the inhibition of the enzyme as well as the triggering of intracellular signaling cascades (Ohnishi et al, 2015; Petrushanko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%